2022
DOI: 10.1177/02654075221092360
|View full text |Cite
|
Sign up to set email alerts
|

Dynamic associations between stress and relationship functioning in the wake of COVID-19: Longitudinal data from the German family panel (pairfam)

Abstract: Individuals all across the world experienced significant disruptions in their personal and family life with the outbreak of the new coronavirus disease 2019 (COVID-19). The current study investigated dynamic associations between stress and relationship functioning over time in the face of the COVID-19 pandemic. Perceived stress, relationship satisfaction, and relationship quality (appreciation, intimacy, conflict) were reported by 1483 young to middle-aged participants who were in a romantic relationship and l… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
11
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(11 citation statements)
references
References 77 publications
(96 reference statements)
0
11
0
Order By: Relevance
“…Therefore, it seems that COVID-19 had a limited impact on couple functioning, at least during May–July 2020. However, it is still unclear why the two studies from the German pairfam project found a decrease in couple functioning (Pauly et al, 2022; Schmid et al, 2021). Further studies are needed to analyze how the sample composition, national context, and exact timing may explain these discrepancies.…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, it seems that COVID-19 had a limited impact on couple functioning, at least during May–July 2020. However, it is still unclear why the two studies from the German pairfam project found a decrease in couple functioning (Pauly et al, 2022; Schmid et al, 2021). Further studies are needed to analyze how the sample composition, national context, and exact timing may explain these discrepancies.…”
Section: Discussionmentioning
confidence: 99%
“…Governments implemented strict social restrictions to contain the pandemic, including physical distancing and reduced social contact. Consequently, individuals experienced significant disruptions in their social lives, particularly those living alone who were forced to spend less time with their social partners (Pauly et al, 2022). These restrictions negatively affected well-being in the short term (Reitsema et al, 2023).…”
Section: Discussionmentioning
confidence: 99%
“…While evidence indicates that COVID-19 and its associated restrictions placed substantial strain on intimate partners, and their relationships, across the general population ( Goodboy et al, 2021 ; Pauley et al, 2022 ), this added strain undoubtedly had more severe consequences for those living with DA. While the circumstances throughout 2020–2021 severely limited the potential for safely acquiring first-person narratives from those living with DA, DAH staff were able to provide crucial third-party insight into the experiences of this vulnerable group in the interim.…”
Section: Discussionmentioning
confidence: 99%
“…These additional stressors put undue strain on relationships generally, with research indicating that couples reported higher levels of partner interference, negative emotions towards interacting with their partners and an increase in relationship turbulence during the outbreak, compared to pre-pandemic ( Goodboy et al, 2021 ). Relationship satisfaction, intimacy and appreciation were also seen to decrease, while relationship conflict increased, from pre-to mid-pandemic, which was found to contribute further to the level of stress experienced by both partners during lockdown ( Pauley et al, 2022 ). For those living with DA, these cumulative stressors served to exacerbate already existing tension and strain within the home, creating what is being referred to as a ‘perfect storm’ ( Women’s Aid, 2020a ).…”
Section: Introductionmentioning
confidence: 94%